The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2217/pgs-2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics in Chronic Pain Therapy: From Disease to Treatment and Challenges for Clinical Practice

Abstract: Pharmacogenomics (PGx) has emerged as an encouraging tool in chronic pain therapy. Genetic variations associated with drug effectiveness or adverse reactions (amitriptyline/nortriptyline/codeine/oxycodone/tramadol-CYP2D6, amitriptyline-CYP2C19, carbamazepine-HLA-A, carbamazepine/oxcarbazepine-HLA-B) can be used to guide chronic pain management. Despite this evidence, many obstacles still need to be overcome for the effective clinical implementation of PGx. To translate the pharmacogenetic testing into actionab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…There is no specific guideline for tramadol, but as tramadol is also a prodrug metabolized through CYP2D6, it seems reasonable to apply the same recommendations as those suggested for codeine, even though tramadol has a more complex mechanism of action [85]. For hydrocodone and oxycodone, further clinical research is still needed to be able to create specific guidelines [81,84,86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no specific guideline for tramadol, but as tramadol is also a prodrug metabolized through CYP2D6, it seems reasonable to apply the same recommendations as those suggested for codeine, even though tramadol has a more complex mechanism of action [85]. For hydrocodone and oxycodone, further clinical research is still needed to be able to create specific guidelines [81,84,86].…”
Section: Discussionmentioning
confidence: 99%
“…This has been clearly illustrated for codeine and tramadol. For hydrocodone and oxycodone, studies show a link with the PK profile of these two drugs, but clinical studies are contradictory and still fail to demonstrate a clear lack of analgesia in PM patients [81,[84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…Data were primarily drawn from AGDS, which is a multi-aim study investigating the risk factors for depression and treatment response to antidepressants. As the AGDS employed phenotyping across an extensive range of complex traits ( 75), on balance it was not feasible to also collect detailed information from participants on dosages and (polypharmacy) combinations taken of the prescribed antidepressants (103); the duration and magnitude of benefits (e.g., for costeffectiveness analyses) (65,104,105); drug tolerability and adverse events (65,(106)(107)(108)(109)(110)(111); adjunct psychological therapies and multidisciplinary treatment/rehabilitation programs (112); other prescribed pain pharmacotherapies and questionnaires (113)(114)(115)(116)(117). Further pharmacoepidemiological studies focusing on chronic pain and a large range of psychiatric comorbidities (51, 52, 118).…”
Section: Strengths Limitations and Further Researchmentioning
confidence: 99%
“…Nevertheless, our large-scale data-driven approach — like recent human genetic 3652 and neuroimaging 5759 antidepressant treatment studies — have revealed novel insights into the relationship between chronic pain and depression. Along with animal model and human pharmacogenetic studies 5356,118,119,123127 , there is also independent converging evidence for the critical role of subcortical brain regions in mediating pain and mood. 128 The application of rigorous statistical genetics methodologies to large-scale neuroimaging data, for example, has already produced several major discoveries, such as advancing our understanding of causal pathways, (subcortical) brain networks and medication response markers in mood disorders.…”
Section: Discussionmentioning
confidence: 99%